The concept of people’s cognitive model as a national and cultural worldview - Kushkimbayeva, Ainur; Dyusembina, Gulsamal; Tutinova, Nurgul; Khalimullina, Naylya (Opción, 2019)
The main goal of the research is to examine national and spiritual values, as well as the artistic and aesthetic attitudes in M. Auezov’s worldview by exploring the author’s dramatic discourse with a focus on verbal-semantic, linguistic-cognitive and pragmatic features of his linguistic personality. As a result, in a dramatic discourse, the cognitive model of the concept people represents country in the conceptual system. In conclusion, the concept of linguistic means people; country has social, ethnographic and aesthetic functions.